Apelin-13 inhibits lipoprotein lipase expression via the APJ/PKCα/miR-361-5p signaling pathway in THP-1 macrophage-derived foam cells. (21st April 2017) - Zhang, Xin; Ye, Qiong; Gong, Duo; Lv, Yuan; Cheng, Haipeng; Huang, Chong; Chen, Lingyan; Zhao, Zhenwang; Li, Liang; Wei, Xie; Zhang, Min; Xia, Xiaodan; et al.
Abstract: Atherosclerotic lesions are characterized by the accumulation of abundant lipids and chronic inflammation. Previous researches have indicated that macrophage-derived lipoprotein lipase (LPL) promotes atherosclerosis progression by accelerating lipid accumulation and pro-inflammatory cytokine secretion. Although apelin-13 has been regarded as an atheroprotective factor, it remains unclear whether it can regulate the expression of LPL. The aim of this study was to explore the effects of apelin-13 on the expression of LPL and the underlying mechanism in THP-1 macrophage-derived foam cells. Apelin-13 significantly decreased cellular levels of total cholesterol, free cholesterol, and cholesterol ester at the concentrations of 10 and 100 nM. ELISA analysis confirmed that treatment with apelin-13 reduced pro-inflammatory cytokine secretion, such as interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α). It was also found that apelin-13 inhibited the expression of LPL as revealed by western blot and real-time PCR analyses. Bioinformatics analyses and dual-luciferase reporter assay indicated that miR-361-5p directly downregulated the expression of LPL by targeting the 3′UTR of LPL. In addition, apelin-13 + miR-361-5p mimic significantly downregulated the expression of LPL in cells. Finally, we demonstrated that apelin-13 downregulated the expression of LPL through activating the activity of PKCα. Taken together, our results showed that apelin-13 downregulated the expression of LPL via activating the APJ/PKCα/miR-361-5p signaling pathway in THP-1 macrophage-derived foam cells, leading to inhibition of lipid accumulation and pro-inflammatory cytokine secretion. Therefore, our studies provide important new insight into the inhibition of lipid accumulation and pro-inflammatory cytokine secretion by apelin-13, and highlight apelin-13 as a promising therapeutic target in atherosclerosis.